ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM Putusan Nomor 34/Pdt.Sus-PHI/2020/PN.Ptk - NIM. A1012191166, VICTORIO NOVIANUS MUSTAHIR (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Unilateral Termination of Employment (PHK) without following legal procedures is a crucial issue in industrial relations and often triggers disputes between workers and employers. One case that is the focus of this study is Decision Number 34/Pdt.Sus-PHI/2020/PN.PTK, which concerns the termination of a supervisor without formal legalproof of alleged serious misconduct. The background of this research is based on the importance of legal protection for workers' normative rights and the need for clarity in judges